2002
DOI: 10.1001/archinte.162.14.1644
|View full text |Cite
|
Sign up to set email alerts
|

Massive Bleeding on a Bladder Protectant

Abstract: Pentosan polysulfate sodium (Elmiron; Alza Pharmaceuticals, Mountain View, Calif) is an oral preparation of pentosan polysulfate used in the symptomatic management of interstitial cystitis. While pentosan polysulfate has a known heparin-like effect in its parenteral form, there have been no previous reports of coagulopathy with oral use. We present an interesting case of inadvertent systemic anticoagulation resulting in serious bleeding complications in a young woman taking oral pentosan polysulfate for inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Despite the low oral bioavailability of Elmiron, cases of bleeding complications such as increases in gastrointestinal bleeding, activated partial thromboplastin time and hematuria have been reported in human cancer patients (Gill et al 2002; Marshall et al 1997; Swain et al 1995). In a Phase I clinical trial in advanced cancer patients, dose limiting toxicity observed included rectal bleeding and ulceration.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the low oral bioavailability of Elmiron, cases of bleeding complications such as increases in gastrointestinal bleeding, activated partial thromboplastin time and hematuria have been reported in human cancer patients (Gill et al 2002; Marshall et al 1997; Swain et al 1995). In a Phase I clinical trial in advanced cancer patients, dose limiting toxicity observed included rectal bleeding and ulceration.…”
Section: Introductionmentioning
confidence: 99%